Rolle von Adipokinen bei der Differenzierung von mesenchymalen Stammzellen - Tsiklauri, Lali; Justus Liebig University Giessen (My University, 2020)
Im Rahmen der Osteoporose ist der altersbedingte Knochenverlust mit einer erhöhten Fettinfiltration im Knochenmark assoziiert. Das osteoporotisch veränderte Hartgewebe wird somit direkt von den Adipozyten des Knochenmarks begrenzt. Angesichts der hohen sekretorischen Aktivitäten der Adipozyten liegt die Hypothese nahe, dass adipozytäre Sekretionsfaktoren wie Adipokine (Visfatin, Leptin und Resistin) die Differenzierung der im Knochenmark befindenden MSC beeinflussen und so zum fortschreitenden Knochenverlust im Rahmen der Osteoporose beitragen. Daher war das Ziel der vorliegenden Arbeit, die Rolle der Adipokine während der Osteogenese sowie Adipogenese in Standardkultur sowie auf aufgereinigten Spongiosafragmenten mit besonderem Fokus auf Matrixumbau zu analysieren.Durch die Adipokine Leptin und Resistin konnten keine Effekte auf die untersuchten Parameter sowohl während der adipogenen als auch osteogenen Differenzierung nachgewiesen werden. Die Stimulierung mit Visfatin führte dagegen zu einem signifikanten Expressionsanstieg von MMPs während der Adipogenese, wobei das Transkriptionsprofil der TIMPs nicht beeinflusst wurde. Interessanterweise reduzierte Visfatin signifikant die Expression von MMPs und TIMPs in osteogen differenzierten MSCs. Die Visfatin-induzierte Dysregulation der MMP- und TIMP-Expression könnte zum gesteigerten Knochenabbau an den Knochen-Knochenmark-Grenzflächen, insbesondere bei geschwächter Knochenmatrix, wie z.B. bei der Osteoporose, beitragen. Des Weiteren resultierte die Stimulierung mit Visfatin in einer signifikant erhöhten Freisetzung von IL6, IL8 und MCP1 sowohl in osteogen als auch adipogen differenzierenden MSCs. Durch die proinflammatorische Wirkung könnte Visfatin negativ auf die Knochenhomöostase wirken, da der osteoklastäre Knochenabbau durch Visfatin-induzierte proinflammatorische Proteine begünstigt würde. Während Visfatin nicht die Expression von adipogenen Markergenen veränderte, konnte in osteogen differenzierten MSCs eine signifikante Induktion von ALP durch Visfatin an Tag 7 der Osteogenese nachgewiesen werden, was eine Visfatin-induzierte Verstärkung der anorganischen Matrixproduktion zur Folge haben könnte. So konnte mittels Alizarin Rot S-Färbung eine erhöhte Mineralisierung durch Visfatin gezeigt werden. Die organische Komponente der EZM, Kollagen Typ I, eines der zentralen Proteine der Knochenplastizität, wurde durch Visfatin an Tag 21 der Osteogenese herrunterreguliert. Dieser differenzielle Effekt von Visfatin auf zwei Komponenten der EZM könnte auf eine gestörte Matrixproduktion durch Visfatin hindeuten und zu einer erhöhten Knochenbrüchigkeit führen. Die Spongiosa-Transfer Experimente zeigten eine signifikante Reduktion der Visfatin-vermittelten Expression von MMPs sowie der proinflammatorischen Zytokine in 3D-Kultur vs. Standardkultur im Verlauf der Adipogenese. Obwohl während der Osteogenese in 3D-Kultur keine Reduktion der Visfatin-induzierten Freisetzung von Entzündungsmediatoren im Vergleich zu Standardkultur erkennbar war, deuten jedoch die während der Adipogenese in 3D-Kultur erzielten Daten auf einen positiven Einfluss der EZM hin.Zur Identifizierung der Signalwege, die bei den Visfatin-vermittelten Effekten während der adipogenen Differenzierung involviert sind, erfolgte die Kostimulierung mit Visfatin und Inhibitoren von p38-MAPK sowie ERK1/2. Während die Inhibierung von p38-MAPK lediglich zu einer Verringerung der MMP13-Expression führte und nicht von Visfatin-induzierten Entzündungsmediatoren, zeigte die Blockierung des ERK1/2-Signalwegs eine nahezu komplette Suppression von MMP13 sowie IL6, IL8 und MCP1. Somit scheint die Aktivierung dieser beiden Signalwege durch Visfatin während der adipogenen Differenzierung von MSCs naheliegend. Insgesamt konnte ein Einfluss des Adipokins Visfatin sowohl bei der Adipogenese als auch der Osteogenese nachgewiesen werden. Während bei der Osteogenese die Visfatin-vermittelten Effekte zur Fragilität des Knochens beitragen könnten, würden Visfatin-induzierte MMPs sowie proinflammatorische Zytokine bei der Adipogenese, zum Knochenabbau beitragen.

Age-related bone loss during osteoporosis is associated with increased fat infiltration into the bone marrow. Thus, bone marrow adipocytes are in a closed contact with altered osteoporotic bone tissue. Adipose tissue and adipocytes are metabolically highly active and express adipokines such as leptin, resistin and visfatin. These adipocyte-derived factors, due to their immunomodulatory functions might influence MSC differentiation and bone homeostasis. MSCs, which can differentiate into adipocytes as well as bone tissue relevant cell types such as osteoblasts, represent the basis of bone formation. In osteoporosis, the differentiation potential of MSCs is shifted towards adipogenesis at the expense of osteogenic differentiation. Therefore, the aim of the study was to analyze the role of central adipokines produced by adipocytes at the bone/bone marrow interface during osteogenic and adipogenic differentiation of MSCs under standard cell culture as well as on purified spongiosa fragments with a special focus on matrix remodeling.The adipokines leptin and resistin showed no effects on the examined parameters during both the adipogenic and the osteogenic differentiation. Stimulation with visfatin led to a significant increased expression of MMPs during adipogenic differentiation. The transcriptional profile of MMP-inhibitors, the TIMPs, was not affected by adipokines. In contrary, a reduction of TIMP expression by visfatin was observed in osteogenically differentiated MSCs. Moreover, a significant reduction of both, MMP2 and 13, could be detected by visfatin during osteogenesis. These observed effects indicate detrimental effects of visfatin on bone metabolism. The visfatin-induced dysregulation of MMP and TIMP expression may interfere with bone remodeling processes and contribute to increased bone turnover at the bone/bone marrow interfaces. Furthermore, stimulation with Visfatin resulted in significantly increased levels of IL6, IL8 and MCP1 during both osteogenic as well as adipogenic differentiation. The observed proinflammatory effect of visfatin may negatively impact bone homeostasis by promoting osteoclastic bone degradation through visfatin-induced proinflammatory proteins.Regarding influence on the differentiation potential of MSCs, no effects of visfatin on adipogenic differentiation capacity could be demonstrated However, during osteogenesis a significant elevated expression of ALP could be observed at 7d after stimulation with visfatin. This could result in a visfatin-induced enhancement of inorganic matrix production as evaluated by Alizarin Red S staining. Osteogenically differentiated cells showed an enhanced mineralized nodule formation in the presence of visfatin. In contrast to mineralization, the organic component of the ECM - Coll.I, responsible for the bone plasticity - was downregulated by visfatin at the last timepoint of osteogenic differentiation. This differential effect of visfatin on two components of ECM could contribute to an altered matrix production leading to increased bone fragility.In general, weaker expression of osteogenic (ALP) and adipogenic (PPARG) marker genes could be observed during differentiation in 3D culture compared to standard cell culture. This indicates a reduced efficiency or delayed differentiation of MSCs in 3D culture. Regarding visfatin-mediated induction of MMPs and cytokines observed in adipogenically differentiated MSCs in 2D culture, an osteoprotective effect of ECM could be demonstrated. The visfatin-induced expression of MMPs as well as the release of proinflammatory cytokines were attenuated during adipogenesis on spongiosa compared to standard cell culture. Although no significant reduction of visfatin-induced release of inflammatory cytokines was observed during osteogenesis in 3D culture compared to standard culture, the data obtained during adipogenesis in 3D culture indicate a protective effect of the ECM.To identify the signaling pathways involved in visfatin-mediated effects during adiopigenic differentiation, cells were costimulated with visfatin and inhibitors of p38 MAPK and ERK1 / 2 signaling pathways. While inhibition of p38 MAPK caused only a reduction in MMP13 expression and did not affect the visfatin-induced release of proinflammatory mediators, the inhibition of the ERK1 / 2 signaling pathway suppressed the expression of MMP13 as well as IL6, IL8 and MCP1. Thus, the involvement of specifically ERK1 /2 signalling in visfatin-mediated effects during adipogenic differentiation of MSCs seems to be important.In summery, an influence of the adipokine Visfatin could be demonstrated in both, adipogenic and osteogenic differentiation of MSCs. While in osteogenesis the visfatin-mediated effects could contribute to increased bone fragility, during adipogenesis Visfatin-induced MMP expression might contribute to the elevated bone loss by directed contact of bone marrow adipocytes with the weakened, demineralized bone matix in osteoporosis.
Role of adipokines during differentiation of mesenchymal stem cells
Keywords: Adipokine; MSC; Adipogenese; Osteogenese; Knochen; adipokines; MSC; adipogenesis; osteogenesis; bone; ddc:500